Becoming the Teacher, I Once Feared English: A Journey from Rural Nepal to Urban Classrooms - Bohara, Bhuban Bahadur (AMC Multidisciplinary Research Journal, 2025)
This autoethnography unearths my reflections to unravel the unpredictable journey from a reluctant student to an English language teacher still striving for professional efficacy. Born into a lower middle-class family in Nepal’s far western hills near the Indian border, I saw no reason to study English—or anything—amid a context of agricultural feudalism. Through anecdotes of missteps, awakenings, and academic shifts, I trace turning points that shaped my professional life. Using the theory of Pratītyasamutpāda (dependent origination), I interpret these events as a causal chain—from ignorance to becoming—while Bourdieu’s concept of linguistic capital provided me insights to assess English’s privileged status. This narrative reveals not just my path but the broader challenge of teaching English dynamically in Nepal, where its value whispers faintly. I found that without causal links, things do not take place; therefore, being an English teacher is the result of various causal links in my educational and career trajectory